The Effectiveness of Phonological-Based Instruction in English As a Foreign Language Students at Primary School Level: A Research Synthesis - Huo, Shuting; Wang, Shufen (Frontiers in Education, 2017)
Phonological-based instruction, namely phonological awareness instruction (PA) and phonics instruction, has shown to be effective on early literacy skills among young children in western countries. Children who learn English as a foreign language (EFL) learn to read English differently from children in English dominant societies. Effectiveness of the instruction in the EFL context is much less investigated. The present study systematically reviewed 15 experimental and quasi-experimental studies published in between 2000 to 2016, on the topic of the effectiveness of phonological-based instruction in the EFL context. Study characteristics and instructional features were described, and effect sizes were calculated. Phonological-based instruction was consistently found to be effective among primary school EFL students on reading underlying skills including phonemic awareness and non-word reading. The median value of the effect size was moderate. In contrast, the effectiveness on word recognition (lexical access and pronunciation) and reading comprehension were inconsistent across studies. The median value of the effect size on word reading was small. This pattern suggests a limitation of the phonological-based instruction, which is the difficulty of transferring the phonological underlying outcomes to real reading. We found that most studies, although meeting the minimum standard of evidence for effectiveness, suffer from methodological flaws, thus they are potentially biased. Therefore, the positive effects reported in this study should be interpreted with caution. The implication for practice of this study is that including phonological-based instruction in the current English curriculum may be beneficial for young EFL students, thus they can better learn to phonologically decode English words. But not enough evidence has been found to support the instructional effectiveness on real word recognition and reading comprehension. Future research on this topic with rigorous design are needed so that strong causal inference can be made. The findings of this study provide novel insights into foreign language education of English for young learners.